Thinking about the long-run economic costs of AIDS - Bell, Clive; Devarajan, Shantayanan; Gersbach, Hans (The macroeconomics of HIV/AIDS, 2004)
Abstract In his book Plagues and Peoples, McNeill (1976) views history as the interplay between an array of parasites and their human hosts—a struggle in which communicable diseases and human responses to them have profound social, economic, and cultural effects. Following the outbreak of the AIDS epidemic in the 1980s, humanity must now contend with a new great plague, the scale and character of which will surely put McNeill’s thesis to the test. One vital lesson to be drawn from his account is that any attempt to understand the effects of the AIDS epidemic must take a long-term perspective. That is a salient feature of the approach we adopt here: we will argue that, from modest beginnings, the economic damage caused by AIDS can assume catastrophic proportions over the long run, and thereby threaten the social fabric itself.